MARKETING STRATEGY FOR TOBACCO AND ITS INDUSTRIAL PRODUCTS TO FACING GLOBAL MARKET AND WORD ANTI-TOBACCO CAMPAIGN - Iryono Iryono (UPT Penerbitan Universitas Jember)
During the last decade, tobacco were have been sharply highlighted by the international community. In global trade, the tobacco business and its industrial products were under pressure from the world through the world health organization that formulates the framework convention on tobacco control (FCTC). The conventions of FCTC aim to control tobacco and its industrial products in the global market, because this product in the signal can be detrimental to health. This paper aims to review the pattern of tobacco trade in a global market that tends to get discriminated against. The method of analysis conducted by the author is to review the existing journals and make observations and discussions related to the problem of tobacco in the global trading. The facts in tobacco trade show that FCTC regulations that have been widely adopted by countries in the world are often tangent to global trade regulations that apply almost all over the world. Tobacco and their industrial products are subject to discriminatory treatment in global trade. This condition has triggered many parties to trade tobacco illegally, given the need of world tobacco despite pressure always rises about 2% every year along with the increase of world population number. In the business administration review, an objective strategy is needed to address the challenges inherent in the tobacco business. The Paradigm of Resources Based View (RBV) and Market Based View (MBV) in the tobacco business needs to be integrated into the internal and external factors of the business, so that the tobacco business can be maintained. For a Country that producing tobacco (for example: Indonesia), the country must supports their citizen to exist at their business, because they get benefit at tobacco business. The Country must safeguard and fight for tobacco to global market without saving to experience product discrimination.